Personal Safety Knowledge of Landsliode Disaster Based on the Application of Adobe Flash CS5 Media at Kindergarten PGRI Tunas Patriot Banjarnegara Regency - Apriliani, Diyan Ayu; Adiarti, Wulan (Jurusan PGPAUD FIP UNNES, 2017)
ABSTRACT Personal safety knowledge of landslide disaster is knowledge of personal security against landslide disaster. Children who are not equipped with personal safety knowledge will have anxiety. A medium that can be used to provide personal safety knowledge in early childhood is by play and pictures. This study aims to determine the difference of adobe flash cs5 media application to personal safety knowledge of landslide disaster in Kindergarten of PGRI Tunas Patriot Banjarnegara Regency. This research uses experimental method with Nonequivalent Control Group Design. The study population is 70 children with 35 children as control group and 35 children as experimental group taken with purposive sampling technique. Moreover, data collection method in this research is test method and documentation method. Hypothesis test results obtained t posttest of control group has no significant difference because the value of 0.340> 0.05, thus personal safety knowledge on landslide disaster before being given the treatment is relatively same. After the treatment in experimental group, there is an increase in personal disaster safety knowledge, as seen from the Sig score. (2 tailed) 0,00 <0,05, therefore in experiment group equal to 137,14 and control group equal to 103,71 with difference of 33,43 and t statistic at posttest equal to -24,185. Based on the description, it can be concluded that adobe flash cs5 media provides enhancement to personal safety knowledge of landslide disaster in children aged 5-6 years. Keywords: Adobe Flash CS5 Media, Personal Safety, Landslide Disaster and 5-6 year old students